A systematic review of solar driven waste to fuel pyrolysis technology for the Australian state of Victoria. (November 2020) - Hamilton, James; Seyedmahmoudian, Mehdi; Jamei, Elmira; Horan, Ben; Stojcevski, Alex
Abstract: Australia's waste management is heavily dependent on landfill. The Australian Bureau of Statistics predicts that as Australia's population and economy grow, there will be a significant increase in the magnitude of waste output. Concentrated solar driven pyrolysis has been identified as a promising means in creating renewable liquid fuel and improving waste management. This technology is based on the upgrading of waste into a valuable commodity. This is of interest to city councils, communities and stakeholders, as both Australia's annual waste generation and energy demands are growing rapidly. This paper provides a case for the implementation of solar-driven pyrolysis for biofuel production in the Australian state of Victoria as well as a comparative analysis of different Renewable Energy Sources and biomass reactions to justify the combination of Concentrated Solar Power with pyrolysis. This study is the first to assess the solar-driven pyrolysis under a Victorian setting. Victoria was chosen due to the comprehensive and readily available waste data kept by its government. The review concluded that a combination of Fresnel Reflector CSP and pyrolysis are best suited for regional Victorian environment. Fresnel reflector technology was found to complement slow pyrolysis well due to its 250–500◦C operating temperature, while regional Victoria was found to be a good trade-off between feedstock distance and DNI exposure. These requirements were important because feedstock transportation was found to cost $AUD 96 per 500km, and it was observed that there could be up to 1200 kWh/m 2 solar exposure difference between Victorian rural and metropolitan locations. This study provides a comprehensive framework of technical requirements pertaining to a Victorian solar-driven pyrolysis system, which will then act as a guidance for future designers.